2013
DOI: 10.1002/bdra.23169
|View full text |Cite
|
Sign up to set email alerts
|

Racial/ethnic disparities in timing of death during childhood among children with congenital heart defects

Abstract: Racial/ethnic differences in mortality were most notably observed during the postneonatal period and early childhood. Future studies should assess factors associated with this disparity in mortality risk for infants with CHDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 45 publications
2
35
0
Order By: Relevance
“…[3][4][5][6][7][8][9]13,26 Variation in study survival rates, which we could not be assessed with our data, could be due to differences in operative techniques, different institution types where surgery is done, inclusion of birth eras with limited potential for surgical intervention, or inclusion of infants with chromosomal anomalies. However, although all studies note stabilization in survival beyond infancy, our study demonstrates relative stability through adolescence.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…[3][4][5][6][7][8][9]13,26 Variation in study survival rates, which we could not be assessed with our data, could be due to differences in operative techniques, different institution types where surgery is done, inclusion of birth eras with limited potential for surgical intervention, or inclusion of infants with chromosomal anomalies. However, although all studies note stabilization in survival beyond infancy, our study demonstrates relative stability through adolescence.…”
Section: Discussionmentioning
confidence: 92%
“…7 This finding of a high survival rate beyond infancy indicates that the most critical and vulnerable period of mortality is the first year of life, and both health care professionals and parents face challenging treatment decisions. [27][28][29] With more families opting for surgery, 30 our finding of a high survival rate beyond infancy also suggests that a growing number of children with HLHS are likely to reach adolescence and adulthood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[93][94][95][96] It is reported that hospital stays after cardiac surgery are longer, and in-hospital mortality rates are higher, among black and Hispanic children than among white children, 97,98 and ethnic variations in mortality rates appear to persist into later childhood. [99][100][101] Although genetic, biological or socioeconomic factors may partly explain racial and ethnic variations, some US authors have suggested that unequal access to diagnosis and care also contributes to differences in mortality. 102,103 However, these findings may not apply within the context of the UK health-care model.…”
Section: Development Of a Risk Model For Death Or Emergency Readmissionmentioning
confidence: 99%
“…These findings complement the results of several recent studies of single state registries which documented significantly higher adjusted hazards (compared with white children) of early childhood death for AAs and Latinos with major birth defects overall 19 and with several specific congenital heart defects. 20,21,22 …”
mentioning
confidence: 99%